Karakteristik dan Efektivitas Lotion Antinyamuk Berbahan Dasar Limbah Kulit Nanas dan Kulit Jeruk Manis - Dewi, Yossie Kharisma; Johan, Vonny Setiaries; AR, Nur Hasnah; Putra, M. Hidayatullah Setia Dharma; Siregar, Erpiani; Diana, Ayu (JURNAL AGROINDUSTRI HALAL, 2025)
One efficient method to prevent infections spread by mosquitoes is to use repellent. However, when used regularly over an extended period, insect repellents containing DEET commonly available on the market may induce adverse effects such as hypersensitivity, irritation, and hives. Pineapple and sweet orange peels can be utilized as natural ingredients in mosquito-repelling lotions because they contain various secondary metabolites, including tannins, saponins, flavonoids, alkaloids, steroids, and essential oils. This study aimed to find the optimal concentration of pineapple peel extract based on the characteristics of the produced mosquito repellent lotion. The experiment used a completely randomized design (CRD), producing 15 experimental units with five treatments—pineapple peel extract concentrations—each with three replications: 2%, 3%, 4%, 5%, and 6%. The lotion with a 6% concentration of pineapple peel extract (LNJ5) was selected due to its homogenous physical characteristics, pH of 7.89, spreadability of 6.98 cm, viscosity of 2131.02 cP, and mosquito protection rate of 88.64%. The lotion had a yellowish-brown color, a faint pineapple and orange scent, and a descriptive organoleptic evaluation that panelists found pleasing